Dinamika sejarah lahirnya Pancasila: Peran tokoh- tokoh bangsa dalam merumuskan Pancasila - Ramadhani, Septya (Maliki Interdisciplinary Journal, 2025)
Pancasila is the foundation of the state that was formed after Indonesian independence, not only as a symbol or theory, but more than that. Pancasila is also a guideline for life that must be applied in national and state life. This article aims to analyze the views and ideas of the figures to from the formulation of the basis of the state. The formulation process was greatly influenced by the roles of several figures, including Soekarno, Moh Yamin, Soepomo and also the committee of nine. However, in this formulation process, there were also several differences of opinion, including those from nationalist groups and Islamic groups, which then led to the formation of the committee of nine. This research uses historical literacy methods, official documents of BPUPKI and PPKI and also speeches by national figures. The role of these figures is not only the ideas they express but also the efforts they make to unite the nation. Thus, the process of formulating Pancasila prioritizes the interests over personal interests, therefore Pancasila is the result of a mutual agreement related to diversity and unity. So, in this article, the role of national figures in formulating Pancasila can influence the life of the nation and state to this day.